Lightweight boron carbide / titanium diboride-based composite ceramic with high-temperature electromagnetic shielding and load bearing functions and preparation method of lightweight boron carbide / titanium diboride-based composite ceramic
By adopting boron carbide/titanium diboride-based composite ceramics, combined with the combination design of B4C and (TixM1-x)B2 and a unique preparation method, the shortcomings of existing electromagnetic shielding materials in load bearing, high-temperature electromagnetic shielding, lightweight and durability are solved, and efficient electromagnetic shielding and excellent mechanical properties are achieved, which are suitable for a variety of complex application scenarios.
Patent Information
- Application Number
- CN202510154137.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-12
- Publication Date
- 2025-04-15
AI Technical Summary
The existing electromagnetic shielding materials have shortcomings in load bearing, high-temperature electromagnetic shielding, lightweight and durability, and cannot meet the needs of many complex application scenarios.
Using boron carbide/titanium diboride-based composite ceramics, a material with high specific hardness, specific strength and specific fracture toughness is designed through the combination of B4C and (TixM1-x)B2, and a composite material with excellent electromagnetic shielding and mechanical properties is obtained through unique preparation methods such as ball milling, rotary evaporation drying, dry press molding, etc.
It realizes lightweight, wear-resistant, corrosion-resistant and high-temperature stability electromagnetic shielding materials, has high efficiency X-band electromagnetic shielding performance, can maintain high electromagnetic shielding performance at high temperatures of 700℃, and has excellent mechanical properties, and is suitable for a variety of complex application scenarios.
Smart Images

Figure CN119822839A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of electromagnetic shielding materials, and in particular to a lightweight boron carbide / titanium diboride-based composite ceramic having both high-temperature electromagnetic shielding and load-bearing functions and a preparation method thereof. Background Art
[0002] With the continuous development of electronic technology, the use of electronic equipment has spread to all aspects of daily life, aerospace and military fields, and electromagnetic pollution has increased dramatically. These sharply increased electromagnetic radiation not only harms human health, but also interferes with the normal operation of other electronic equipment, causing them to malfunction. In order to avoid the harm of electromagnetic radiation, electromagnetic shielding materials are indispensable.
[0003] Traditional electromagnetic shielding materials are mainly metals, such as stainless steel, copper, silver, etc. However, they are usually easy to oxidize, not corrosion-resistant, and have high specific gravity and poor wear resistance, which limits their application. Although the recently emerging carbon-based and polymer-based electromagnetic shielding materials are lightweight, they have poor high-temperature stability and poor mechanical properties. In application scenarios where load bearing, high-temperature electromagnetic shielding and durability are all required, they will not meet the requirements.
[0004] Disadvantages of existing technology:
[0005] 1. Metal electromagnetic shielding materials have high density, are easy to oxidize, and have poor corrosion resistance and wear resistance;
[0006] 2. Lightweight carbon-based and polymer-based electromagnetic shielding materials have poor high-temperature stability and poor mechanical properties.
[0007] Therefore, they cannot be used in applications where load bearing, high temperature electromagnetic shielding, light weight and durability are all required. Summary of the invention
[0008] In view of the technical problems existing in the prior art, the purpose of the present invention is to propose a lightweight boron carbide / titanium diboride-based composite ceramic with both high-temperature electromagnetic shielding and load-bearing functions and a preparation method thereof, and to obtain an electromagnetic shielding material that is lightweight, wear-resistant, corrosion-resistant, has good high-temperature stability, and has excellent mechanical properties. It has both high-temperature electromagnetic shielding and load-bearing functions, so as to obtain an electromagnetic shielding material that meets the needs of more application scenarios.
[0009] To achieve the above object, the present invention is implemented by the following technical solutions:
[0010] On the one hand, the present invention provides a lightweight boron carbide / titanium diboride-based composite ceramic with both high-temperature electromagnetic shielding and load-bearing functions, wherein the composite ceramic is composed of B4C and a single phase (Ti x M 1-x)B2 solid solution as the main component, wherein M is any one of Cr, Mo, Ni, Zr, Mn, W, Ta, Hf, V, Nb and Sc, and 0.5≤x≤1.
[0011] As a further optimization scheme of the present invention, the B4C and (Ti x M 1-x )The molar ratio of B2 is 1:0.5 to 1:1.5.
[0012] As a further optimization scheme of the present invention, the density of the composite ceramic is 2.9-4.9 g / cm 3 .
[0013] As a further optimization scheme of the present invention, the specific hardness of the composite ceramic is 8.7 to 13.5 GPa·cm 3 ·g -1 , specific strength is 160~210MPa, specific fracture toughness is 1.2~2.0MPa·m 1 / 2 cm 3 ·g -1 .
[0014] As a further optimization scheme of the present invention, at room temperature, the total electromagnetic shielding effectiveness of the composite ceramic in the X-band exceeds 40dB, and can shield more than 99.99% of X-band electromagnetic waves; at a high temperature of 700°C, the total electromagnetic shielding effectiveness of the composite ceramic in the X-band exceeds 30dB, and can shield more than 99.9% of X-band electromagnetic waves.
[0015] As a further optimization scheme of the present invention, there are a large number of nano twins and stacking faults in the B4C in the composite ceramic. x M 1-x )There are lattice distortion and high-density dislocations in B2.
[0016] On the other hand, the present invention provides a method for preparing the lightweight boron carbide / titanium diboride-based composite ceramic having both high-temperature electromagnetic shielding and load-bearing functions, the preparation method comprising any one of the following three methods:
[0017] Method 1:
[0018] Step 1.1, weighing and mixing one of commercially available Cr3C2, Mo2C, Ni3C, ZrC, Mn3C, WC, TaC, HfC, VC and NbC powders and TiC powder according to the chemical reaction equation (1), adding an organic solvent and a grinding ball, and mixing by ball milling for a certain period of time to obtain a powder slurry, and then drying and sieving by rotary evaporation to obtain a uniformly mixed powder;
[0019] xTiC+(1-x)MCy =(Ti x M 1-x )C x+y-xy (1)
[0020] Step 1.2: dry-press and vacuum-calcine the mixed powder obtained in step 1.1 to obtain (Ti x M 1-x )C x+y-xy The powder block is crushed, ground and sieved to obtain (Ti x M 1-x )C x+y-xy Powder;
[0021] Step 1.3: The (Ti x M 1-x )C x+y-xy The powder and commercially available B powder and B4C powder are weighed and mixed according to the chemical reaction equation (2), and an organic solvent and grinding balls are added. After ball milling for a certain period of time, a powder slurry is obtained, and then the powder is dried by rotary evaporation and sieved to obtain a uniformly mixed powder.
[0022] (Ti x M 1-x )C x+y-xy +(2+4x+4y-4xy)B+zB4C=(Ti x M 1-x )B2+(x+y-xy+z)B4C (2)
[0023] In formula (1) and formula (2), 0.5≤x≤1, y=0.33, 0.5, 0.67 or 1, 0.67≤x+y-xy+z≤2;
[0024] Step 1.4, pouring the mixed powder obtained in step 1.3 into a graphite mold or forming it by dry pressing or cold isostatic pressing, and then hot pressing sintering, spark plasma sintering or pressureless sintering at a certain temperature and pressure to obtain a lightweight boron carbide / titanium diboride-based composite ceramic with both high-temperature electromagnetic shielding and load-bearing functions;
[0025] Method 2:
[0026] Step 2.1, weigh and mix one of the commercially available CrB2, MoB2, ZrB2, MnB2, WB2, TaB2, HfB2, VB2, NbB2 and ScB2 powders with TiB2 powder and B4C powder according to the chemical reaction equation (3), add an organic solvent and a grinding ball, and mix the mixture by ball milling for a certain period of time to obtain a powder slurry, and then dry and sieve the mixture by rotary evaporation to obtain a uniformly mixed powder;
[0027] xTiB2+(1-x)MB2+mB4C=(Ti x M 1-x )B2+mB4C (3)
[0028] In formula (3), 0.5≤x≤1, 0.67≤m≤2;
[0029] Step 2.2, pouring the mixed powder obtained in step 2.1 into a graphite mold or forming it by dry pressing or cold isostatic pressing, and then hot pressing sintering, spark plasma sintering or pressureless sintering at a certain temperature and pressure to obtain a lightweight boron carbide / titanium diboride-based composite ceramic with both high-temperature electromagnetic shielding and load-bearing functions;
[0030] Method 3:
[0031] Step 3.1, weigh and mix one of the commercially available Cr2O3, Mo2O3, NiO, ZrO2, MnO, WO3, Ta2O5, HfO2, V2O5, Nb2O5 and Sc2O3 powders with TiO2 powder, B4C powder, carbon powder or graphite powder according to the chemical reaction equation (4); in order to ensure the complete reaction, the B4C powder must be appropriately excessive, and the carbon powder or graphite powder must be appropriately deficient during mixing; then, the weighed powders, an appropriate amount of organic solvent and a certain amount of grinding balls are placed in a ball mill, and after ball milling for a certain period of time, a powder slurry is obtained, which is then dried by rotary evaporation and sieved to obtain a uniformly mixed powder;
[0032] xTiO2+(1-x)MO p +(2x+p-px-0.5)C+(0.5+m)B4C=(Ti x M 1-x )B2+mB4C+(2x+p-px)CO(4)
[0033] In formula (4), 0.5≤x≤1, 0.67≤m≤2, p=1, 1.5, 2, 2.5 or 3;
[0034] Step 3.2: pour the mixed powder obtained in step 3.1 into a graphite mold, and perform hot pressing sintering or spark plasma sintering on it through multiple steps of heat preservation at a certain temperature and pressure to obtain a lightweight boron carbide / titanium diboride-based composite ceramic with both high-temperature electromagnetic shielding and load-bearing functions.
[0035] As a further optimization scheme of the present invention, the purity of all commercially available raw materials in steps 1.1, 1.3, 2.1 and 3.1 is ≥99%, and the average particle size is 0.1-10 μm; the ball milling mixing time in steps 1.1, 1.3, 2.1 and 3.1 is 2-24 h.
[0036] As a further optimization scheme of the present invention, the sintering temperature in steps 1.4 and 2.2 is 1700-2100°C, the sintering pressure is 0-200MPa, the holding time is 10-120min, the sintering environment conditions are vacuum or argon atmosphere, and the heating rate is 10-200°C / min; the vacuum calcination temperature in step 2.2 is 1200-1900°C, and the calcination time is 0.5-2h.
[0037] As a further optimization scheme of the present invention, the sintering system in step 3.2 is as follows: first, the temperature is raised to 1500-1800°C at a heating rate of 10-200°C / min, and after being kept at this temperature for 10-90 minutes, the temperature is further raised to 1700-2100°C at a heating rate of 10-200°C / min, and the sintering pressure is uniformly increased to 30-200MPa, and then maintained at this temperature and pressure for 10-120 minutes, and finally cooled to room temperature with the furnace. The sintering environment conditions are vacuum or argon atmosphere.
[0038] Compared with the prior art, the boron carbide / titanium diboride-based composite ceramics prepared by the present invention, through unique composition design and microstructure regulation, show significant beneficial effects in terms of light weight, electromagnetic shielding performance, high temperature stability, mechanical properties and performance regulation, and can meet the needs of a variety of complex application scenarios. The details are as follows:
[0039] 1. The density of the composite ceramic of the present invention is 2.9-4.9 g / cm 3 Compared with traditional metal electromagnetic shielding materials, such as stainless steel, copper, silver, etc., the density is greatly reduced. Due to the high density of traditional metal materials, their use is limited in application scenarios with strict weight requirements, such as the aerospace field. The lightweight characteristics of the present invention make it have greater application potential in these fields, which can effectively reduce the weight of equipment and improve energy efficiency.
[0040] 2. In the room temperature X-band, the total electromagnetic shielding effectiveness exceeds 40dB, which can shield more than 99.99% of X-band electromagnetic waves; at high temperature (700°C), the total electromagnetic shielding effectiveness of the X-band exceeds 30dB, which can shield more than 99.9% of X-band electromagnetic waves. Compared with the emerging carbon-based and polymer-based electromagnetic shielding materials, the high-temperature electromagnetic shielding performance of the composite ceramics of the present invention is significantly superior. Carbon-based and polymer-based materials have poor high-temperature stability, and their electromagnetic shielding performance will drop significantly in high-temperature environments, which cannot meet the electromagnetic shielding requirements in high-temperature environments such as aerospace and military. The materials of the present invention can effectively solve this problem.
[0041] 3. Under the high temperature environment of 700℃, it can still maintain a high electromagnetic shielding efficiency, indicating that it has good high temperature stability. This is due to the B4C and (Ti x M 1-x) The special structure and composition of B2. Traditional metal electromagnetic shielding materials are easily oxidized at high temperatures, resulting in performance degradation, while the material of the present invention overcomes this shortcoming and broadens its application range in high temperature environments.
[0042] 4. High specific hardness (8.7~13.5GPa·cm 3 ·g -1 ), specific strength (160~210MPa·cm 3 ·g -1 ) and specific fracture toughness (1.2~2.0MPa·m 1 / 2 cm 3 ·g -1 ). Unlike carbon-based and polymer-based electromagnetic shielding materials with poor mechanical properties, the composite ceramics of the present invention can withstand larger loads. In application scenarios that need to withstand certain pressures and impact forces, such as structural components of aerospace equipment, they can not only play the role of electromagnetic shielding, but also bear loads, thereby improving the structural stability and reliability of the equipment.
[0043] 5. Simply by adjusting the content, element types and proportions of titanium diboride-based solid solutions in composite ceramics, a multifunctional ceramic material with light weight, excellent electromagnetic shielding and mechanical properties, high-temperature electromagnetic shielding and load-bearing functions can be obtained, and the dominant mechanism of its electromagnetic shielding (absorption-dominant or reflection-dominant) can be adjusted. This controllability of performance enables the material to be customized according to different application requirements, greatly improving the applicability of the material and providing the possibility for its wide application in various fields. BRIEF DESCRIPTION OF THE DRAWINGS
[0044] Figure 1 XRD diffraction patterns of boron carbide-titanium diboride based composite ceramics prepared in Examples 1, 2 and 3.
[0045] Figure 2 This is a microscopic morphology of the boron carbide-titanium diboride based composite ceramic prepared in Example 1. DETAILED DESCRIPTION
[0046] In order to enable those skilled in the art to better understand the technical solution of the present invention, the preferred implementation scheme of the present invention is described below in conjunction with specific embodiments, but it should not be understood as limiting the present invention and is only used as an example.
[0047] The experimental methods or test methods described in the following examples are conventional methods unless otherwise specified; the reagents and materials are obtained from conventional commercial channels or prepared by conventional methods unless otherwise specified.
[0048] Example 1
[0049] Step 1: Weigh 44.99g of commercially available TiC powder and 5.01g of commercially available Cr3C2 powder respectively, and add the weighed powder (a total of 50g), 50g of anhydrous ethanol and 100g of yttrium-stabilized zirconia balls (mass ratio of balls is 1:2) into a ball mill and mix for 24h. Then, dry the obtained slurry at 60°C by rotary evaporation for 25min and pass it through a 120-mesh sieve to obtain a uniform and dry mixed powder.
[0050] Step 2: Weigh 10g of the above mixed powder and dry press (molding pressure 100MPa, holding time 2min) to obtain a mixed powder body, repeat this step 3-4 times. Then, the obtained mixed powder body is vacuum calcined at 1650℃ for 1.5h to obtain (Ti 0.9 Cr 0.1 )C 0.97 The heating rate of the powder block during vacuum calcination was 10°C / min. 0.7 Cr 0.3 )C 0.97 The powder block was crushed and passed through a 300-mesh sieve to obtain (Ti 0.7 Cr 0.3 )C 0.97 powder.
[0051] Step 3: Weigh 30 g of (Ti 0.7 Cr 0.3 )C 0.97 The powder and 31.76g of commercially available B powder were added together with the weighed powder (a total of 61.76g), 61.76g of anhydrous ethanol and 123.52g of yttrium-stabilized zirconia balls (mass ratio of the balls was 1:2) and the mixture was milled for 24h. Then, the obtained slurry was dried at 60°C for 40min by rotary evaporation and passed through a 120-mesh sieve to obtain a uniform and dry mixed powder.
[0052] Step 4: Weigh about 20g of the mixed powder obtained in step 3 and pour it into a graphite mold with an inner diameter of 40mm, and use 0.15mm thick carbon paper to separate the powder from the inner wall of the mold sleeve. Then, it is pressure sintered by spark plasma sintering equipment, and the sintering environment conditions are vacuum. The specific sintering system is: heat up to 500℃ at a heating rate of 100℃ / min, and the pressure applied to the sample is constant at 10MPa; then, heat up to 1950℃ at a heating rate of 100℃ / min, and the pressure applied to the sample is uniformly increased to 60MPa, and maintained at this temperature and pressure for 10min. After the heat and pressure are maintained, the pressure applied to the sample is reduced to 10MPa and heating is stopped, and then cooled to room temperature with the furnace.
[0053] XRD phase analysis ( Figure 1 ) shows that the B4C-(Ti 0.9 Cr 0.1 )B2 composite ceramics contain only B4C and single phase (Ti 0.9 Cr 0.1 )B2 solid solution. Microscopic morphology ( Figure 2 ) shows that the B4C-(Ti 0.9 Cr 0.1 )B2 composite ceramics are highly dense, have no obvious residual pores, and show obvious black and gray-white phases. The black phase is B4C and the gray-white phase is (Ti 0.9 Cr 0.1 )B2 (average grain size is about 1μm). There are a lot of nano twins and stacking faults in the B4C phase of the composite ceramic. 0.9 Cr 0.1 )There are high-density dislocations and severe lattice distortion in the B2 phase.
[0054] The B4C-(Ti 0.9 Cr 0.1 )B2 composite ceramic density is 3.33g / cm 3 , density is 98.8%, B4C and (Ti 0.9 Cr 0.1 The total electromagnetic shielding effectiveness (SE) of the composite ceramic at room temperature is T ) exceeds 45dB in the entire X-band, which means that it can shield more than 99.996% of X-band electromagnetic waves. Its main electromagnetic shielding mechanism is absorption loss. In the entire X-band, absorption loss (SE A ,~29dB) are significantly higher than the reflection loss (SE R ,~16dB). At high temperature (700℃), the total electromagnetic shielding effectiveness (SE T ) exceeds 34dB in the entire X-band, which means that it can shield more than 99.96% of X-band electromagnetic waves. Its main electromagnetic shielding mechanism is absorption loss. In addition, the composite ceramic has a high specific hardness (13.50GPa·cm 3 ·g -1 ), specific strength (207.2MPa·cm 3 ·g -1 ) and specific fracture toughness (1.681MPa·m 1 / 2 cm 3 ·g -1 These properties show that the B4C-(Ti 0.9 Cr 0.1)B2 composite ceramic is a lightweight, multifunctional ceramic material that has both high-temperature electromagnetic shielding and load-bearing functions.
[0055] Example 2
[0056] Step 1: Weigh 34.98g of commercially available TiC powder and 15.02g of commercially available Cr3C2 powder respectively, and add the weighed powder (a total of 50g), 50g of anhydrous ethanol and 100g of yttrium-stabilized zirconia balls (mass ratio of balls is 1:2) into a ball mill and mix for 24h. Then, dry the obtained slurry at 60°C by rotary evaporation for 25min and pass it through a 120-mesh sieve to obtain a uniform and dry mixed powder.
[0057] Step 2: Weigh 10g of the above mixed powder and dry press (molding pressure 100MPa, holding time 2min) to obtain a mixed powder body, repeat this step 3-4 times. Then, the obtained mixed powder body is vacuum calcined at 1650℃ for 1.5h to obtain (Ti 0.7 Cr 0.3 )C 0.9 The heating rate of the powder block during vacuum calcination was 10°C / min. 0.7 Cr 0.3 )C 0.9 The powder block was crushed and passed through a 300-mesh sieve to obtain (Ti 0.7 Cr 0.3 )C 0.9 powder.
[0058] Step 3: Weigh 30 g of (Ti 0.7 Cr 0.3 )C 0.9 The powder and 30.31g of commercially available B powder were added together with the weighed powder (a total of 60.31g), 60.31g of anhydrous ethanol and 120.62g of yttrium-stabilized zirconia balls (mass ratio of the balls was 1:2) and the mixture was milled for 24h. Then, the obtained slurry was dried at 60°C for 40min by rotary evaporation and passed through a 120-mesh sieve to obtain a uniform and dry mixed powder.
[0059] Step 4: Weigh about 21g of the mixed powder obtained in step 3 and pour it into a graphite mold with an inner diameter of 40mm, and use 0.15mm thick carbon paper to separate the powder from the inner wall of the mold sleeve. Then, it is pressure sintered by spark plasma sintering equipment, and the sintering environment condition is vacuum. The specific sintering system is: heat up to 500℃ at a heating rate of 100℃ / min, and the pressure applied to the sample is constant at 10MPa; then, heat up to 1950℃ at a heating rate of 100℃ / min, and the pressure applied to the sample is uniformly increased to 60MPa, and maintained at this temperature and pressure for 10min. After the heat and pressure are maintained, the pressure applied to the sample is reduced to 10MPa and heating is stopped, and then cooled to room temperature with the furnace.
[0060] XRD phase analysis ( Figure 1 ) shows that the B4C-(Ti 0.7 Cr 0.3 )B2 composite ceramics contain only B4C and single phase (Ti 0.7 Cr 0.3 )B2 solid solution (average grain size is about 1.3μm). There are a lot of nano twins and stacking faults in the B4C phase of the composite ceramic. 0.7 Cr 0.3 )There are high-density dislocations and severe lattice distortion in the B2 phase.
[0061] The B4C-(Ti 0.7 Cr 0.3 )B2 composite ceramic density is 3.41g / cm 3 , density is 98.6%, B4C and (Ti 0.7 Cr 0.3 The total electromagnetic shielding effectiveness (SE) of the composite ceramic at room temperature is T ) exceeds 43dB in the entire X-band, which means that it can shield more than 99.994% of X-band electromagnetic waves. Its main electromagnetic shielding mechanism is absorption loss. In the entire X-band, the absorption loss (~25dB) is significantly higher than the reflection loss (~18dB). At high temperature (700℃), the total electromagnetic shielding effectiveness (SE T ) exceeds 32dB in the entire X-band, which means that it can shield more than 99.93% of X-band electromagnetic waves. Its main electromagnetic shielding mechanism is absorption loss. In addition, the composite ceramic has a high specific hardness (12.73GPa·cm 3 ·g -1 ), specific strength (196.8MPa·cm 3 ·g -1 ) and specific fracture toughness (1.848MPa·m 1 / 2 cm3 ·g -1 These properties show that the B4C-(Ti 0.7 Cr 0.3 )B2 composite ceramic is a lightweight, multifunctional ceramic material that has both high-temperature electromagnetic shielding and load-bearing functions.
[0062] Example 3
[0063] Step 1: Weigh 16.17g of commercially available TiB2 powder, 26.13g of commercially available CrB2 powder and 32.69g of commercially available B4C powder respectively, and add the weighed powder (75g in total), 75g of anhydrous ethanol and 150g of yttrium-stabilized zirconia balls (mass ratio of balls is 1:2) into a ball mill and mix for 24h. Then, the obtained slurry is dried at 60°C for 35min by rotary evaporation and passed through a 120-mesh sieve to obtain a uniform and dry mixed powder.
[0064] Step 2: Weigh about 22g of the mixed powder obtained in step 1 and pour it into a graphite mold with an inner diameter of 40mm, and use 0.15mm thick carbon paper to separate the powder from the inner wall of the mold sleeve. Then, it is pressure sintered by spark plasma sintering equipment, and the sintering environment conditions are vacuum. The specific sintering system is: heat up to 450℃ at a heating rate of 100℃ / min, and the pressure applied to the sample is constant at 10MPa; then, heat up to 1850℃ at a heating rate of 100℃ / min, and the pressure applied to the sample is uniformly increased to 60MPa, and maintained at this temperature and pressure for 10min. After the heat and pressure are maintained, the pressure is released and the heating is stopped, and the furnace is cooled to room temperature.
[0065] XRD phase analysis ( Figure 1 ) shows that the B4C-(Ti 0.5 Cr 0.5 )B2 composite ceramics contain only B4C and single phase (Ti 0.5 Cr 0.5 )B2 solid solution (average grain size is about 1.5μm). There are a lot of nano twins and stacking faults in the B4C phase of the composite ceramic. 0.5 Cr 0.5 )There are high-density dislocations and severe lattice distortion in the B2 phase.
[0066] The B4C-(Ti 0.5 Cr 0.5 )B2 composite ceramic density is 3.52g / cm 3 , density is 98.6%, B4C and (Ti 0.5 Cr 0.5The total electromagnetic shielding effectiveness (SE) of the composite ceramic at room temperature is T ) exceeds 41dB in the entire X-band, which means that it can shield more than 99.992% of X-band electromagnetic waves. Its main electromagnetic shielding mechanism is absorption loss. In the entire X-band, the absorption loss (~24dB) is higher than the reflection loss (~17.5dB). At high temperature (700℃), the total electromagnetic shielding effectiveness (SE T ) exceeds 31dB in the entire X-band, which means that it can shield more than 99.92% of X-band electromagnetic waves. Its main electromagnetic shielding mechanism is absorption loss. In addition, the composite ceramic has a high specific hardness (11.40GPa·cm 3 ·g -1 ), specific strength (181MPa·cm 3 ·g -1 ) and specific fracture toughness (1.461MPa·m 1 / 2 cm 3 ·g -1 These properties show that the B4C-(Ti 0.5 Cr 0.5 )B2 composite ceramic is a lightweight, multifunctional ceramic material that has both high-temperature electromagnetic shielding and load-bearing functions.
[0067] Example 4
[0068] Step 1: Weigh 16.77g of commercially available TiO2 powder, 17.25g of commercially available ZrO2 powder, 12.19g of commercially available B4C powder and 3.78g of commercially available graphite powder respectively, and add the weighed powder (a total of 50g), 50g of anhydrous ethanol and 100g of yttrium-stabilized zirconia balls (mass ratio of balls is 1:2) into a ball mill and mix for 24h. Then, the obtained slurry is dried at 60°C for 30min by rotary evaporation and passed through a 120-mesh sieve to obtain a uniform and dry mixed powder.
[0069] Step 2: Weigh about 39g of the mixed powder obtained in step 1 and pour it into a graphite mold with an inner diameter of 40mm, and use 0.15mm thick carbon paper to separate the powder from the inner wall of the mold sleeve. Then, it is sintered by hot pressing sintering equipment, and the sintering environment condition is vacuum. The specific sintering system is: first, the temperature is increased to 1600℃ at a heating rate of 10℃ / min, and after keeping the temperature for 30min, it is continued to be heated to 1900℃ at a heating rate of 10℃ / min. At the same time, the pressure applied to the sample is uniformly increased to 50MPa, and maintained at this temperature and pressure for 2h. After the insulation and pressure are completed, the pressure is released and the heating is stopped, and the furnace is cooled to room temperature.
[0070] The B4C-(Ti0.6 Zr 0.4 )B2 composite ceramics contain only B4C and single phase (Ti 0.6 Zr 0.4 )B2 solid solution (average grain size is about 1.6μm). There are a lot of nano twins and stacking faults in the B4C phase of the composite ceramic. 0.6 Zr 0.4 )There are high-density dislocations and severe lattice distortion in the B2 phase.
[0071] The B4C-(Ti 0.6 Zr 0.4 )B2 composite ceramic density is 3.60g / cm 3 , density is 98.4%, B4C and (Ti 0.6 Zr 0.4 )B2 has a molar ratio of 1:1. The total electromagnetic shielding effectiveness (SE) of the composite ceramic at room temperature T ) exceeds 40dB in the entire X-band, which means that it can shield more than 99.99% of X-band electromagnetic waves. Its main electromagnetic shielding mechanism is reflection loss. In the entire X-band, the absorption loss (~19dB) is slightly lower than the reflection loss (~21dB). At high temperature (700℃), the total electromagnetic shielding effectiveness (SE T ) exceeds 30dB in the entire X-band, which means that it can shield more than 99.9% of X-band electromagnetic waves. Its main electromagnetic shielding mechanism is reflection loss. In addition, the composite ceramic has a high specific hardness (11.17GPa·cm 3 ·g -1 ), specific strength (186.1MPa·cm 3 ·g -1 ) and specific fracture toughness (1.489MPa·m 1 / 2 cm 3 ·g -1 These properties show that the B4C-(Ti 0.6 Zr 0.4 )B2 composite ceramic is a lightweight, multifunctional ceramic material that has both high-temperature electromagnetic shielding and load-bearing functions.
[0072] Example 5
[0073] Step 1: Weigh 9.73g of commercially available TiB2 powder, 9.32g of commercially available ScB2 powder and 30.95g of commercially available B4C powder respectively, and add the weighed powder (a total of 50g), 50g of anhydrous ethanol and 100g of yttrium-stabilized zirconia balls (mass ratio of balls is 1:2) into a ball mill and mix for 24h. Then, the obtained slurry is dried at 60°C for 25min by rotary evaporation and passed through a 120-mesh sieve to obtain a uniform and dry mixed powder.
[0074] Step 2: Weigh about 20g of the mixed powder obtained in step 1 and pour it into a graphite mold with an inner diameter of 40mm, and use 0.15mm thick carbon paper to separate the powder from the inner wall of the mold sleeve. Then, it is pressure sintered by spark plasma sintering equipment, and the sintering environment conditions are vacuum. The specific sintering system is: heat up to 600℃ at a heating rate of 100℃ / min, and the pressure applied to the sample is constant at 10MPa; then, heat up to 1850℃ at a heating rate of 100℃ / min, and the pressure applied to the sample is uniformly increased to 100MPa, and maintained at this temperature and pressure for 10min. After the heat and pressure are maintained, the pressure is released and the heating is stopped, and the furnace is cooled to room temperature.
[0075] The B4C-(Ti 0.5 Sc 0.5 )B2 composite ceramics contain only B4C and single phase (Ti 0.5 Sc 0.5 )B2 solid solution (average grain size is about 1.2μm). There are a lot of nano twins and stacking faults in the B4C phase of the composite ceramic. 0.5 Sc 0.5 )There are high-density dislocations and severe lattice distortion in the B2 phase.
[0076] The B4C-(Ti 0.5 Sc 0.5 )B2 composite ceramic density is 2.90g / cm 3 , density is 98.4%, B4C and (Ti 0.5 Sc 0.5 The total electromagnetic shielding effectiveness (SE) of the composite ceramic at room temperature is T ) exceeds 46dB in the entire X-band, which means that it can shield more than 99.99% of X-band electromagnetic waves. Its main electromagnetic shielding mechanism is absorption loss. In the entire X-band, the absorption loss (~30dB) is higher than the reflection loss (~16dB). At high temperature (700℃), the total electromagnetic shielding effectiveness (SE T) exceeds 35dB in the entire X-band, which means that it can shield more than 99.96% of X-band electromagnetic waves. Its main electromagnetic shielding mechanism is absorption loss. In addition, the composite ceramic has a high specific hardness (12.84GPa·cm 3 ·g -1 ), specific strength (209.3MPa·cm 3 ·g -1 ) and specific fracture toughness (1.966MPa·m 1 / 2 cm 3 ·g -1 These properties show that the B4C-(Ti 0.5 Sc 0.5 )B2 composite ceramic is a lightweight, multifunctional ceramic material that has both high-temperature electromagnetic shielding and load-bearing functions.
[0077] Example 6
[0078] Step 1: Weigh 21g of commercially available TiB2 powder, 9.92g of commercially available MnB2 powder and 19.08g of commercially available B4C powder respectively, and add the weighed powder (a total of 50g), 50g of anhydrous ethanol and 100g of yttrium-stabilized zirconia balls (mass ratio of balls is 1:2) into a ball mill and mix for 24h. Then, dry the obtained slurry at 60°C for 45min by rotary evaporation and pass through a 120-mesh sieve to obtain a uniform and dry mixed powder.
[0079] Step 2: Weigh about 22g of the mixed powder obtained in step 1, and successively dry press (molding pressure 120MPa, holding time 1min) and cold isostatic press (molding pressure 200MPa, holding time 10min) to obtain a green body with a diameter of about 45mm and a thickness of about 10mm. Subsequently, the green body is placed in a pressureless sintering furnace for pressureless sintering, and the sintering environment condition is an argon atmosphere. The specific sintering system is: heat up to 1900℃ at a heating rate of 10℃ / min and maintain at this temperature for 2h. After the insulation is completed, stop heating and cool to room temperature with the furnace.
[0080] The B4C-(Ti 0.7 Mn 0.3 )B2 composite ceramics contain only B4C and single phase (Ti 0.7 Mn 0.3 )B2 solid solution (average grain size is about 3μm). There are a lot of nano twins and stacking faults in the B4C phase of the composite ceramic. 0.7 Mn 0.3 )There are high-density dislocations and severe lattice distortion in the B2 phase.
[0081] The B4C-(Ti0.7 Mn 0.3 )B2 composite ceramic density is 3.46g / cm 3 , density is 97.5%, B4C and (Ti 0.6 Zr 0.4 The total electromagnetic shielding effectiveness (SE) of the composite ceramic at room temperature is T ) exceeds 40dB in the entire X-band, which means that it can shield more than 99.99% of X-band electromagnetic waves. Its main electromagnetic shielding mechanism is absorption loss. In the entire X-band, the absorption loss (~27dB) is significantly higher than the reflection loss (~13dB). At high temperature (700℃), the total electromagnetic shielding effectiveness (SE T ) exceeds 30dB in the entire X-band, which means that it can shield more than 99.9% of X-band electromagnetic waves. Its main electromagnetic shielding mechanism is absorption loss. In addition, the composite ceramic has a high specific hardness (8.73GPa·cm 3 ·g -1 ), specific strength (164.2MPa·cm 3 ·g -1 ) and specific fracture toughness (1.237MPa·m 1 / 2 cm 3 ·g -1 These properties show that the B4C-(Ti 0.6 Zr 0.4 )B2 composite ceramic is a lightweight, multifunctional ceramic material that has both high-temperature electromagnetic shielding and load-bearing functions.
[0082] Example 7
[0083] Step 1: Weigh 21.57g of commercially available TiB2 powder, 9.12g of commercially available MoB2 powder and 19.31g of commercially available B4C powder respectively, and add the weighed powder (a total of 50g), 50g of anhydrous ethanol and 100g of yttrium-stabilized zirconia balls (mass ratio of balls is 1:2) into a ball mill and mix for 24h. Then, the obtained slurry is dried at 70°C for 35min by rotary evaporation and passed through a 120-mesh sieve to obtain a uniform and dry mixed powder.
[0084] Step 2: Weigh about 23g of the mixed powder obtained in step 1 and pour it into a graphite mold with an inner diameter of 40mm, and use 0.15mm thick carbon paper to separate the powder from the inner wall of the mold sleeve. Then, it is pressure sintered by spark plasma sintering equipment, and the sintering environment conditions are vacuum. The specific sintering system is: heat up to 600℃ at a heating rate of 100℃ / min, and the pressure applied to the sample is constant at 10MPa; then, heat up to 1850℃ at a heating rate of 100℃ / min, and the pressure applied to the sample is uniformly increased to 60MPa, and maintained at this temperature and pressure for 10min. After the heat and pressure are maintained, the pressure is released and the heating is stopped, and the furnace is cooled to room temperature.
[0085] The B4C-(Ti 0.8 Mo 0.2 )B2 composite ceramics contain only B4C and single phase (Ti 0.8 Mo 0.2 )B2 solid solution (average grain size is about 1.1μm). There are a lot of nano twins and stacking faults in the B4C phase of the composite ceramic. 0.8 Mo 0.2 )There are high-density dislocations and severe lattice distortion in the B2 phase.
[0086] The B4C-(Ti 0.8 Mo 0.2 )B2 composite ceramic density is 3.59g / cm 3 , density is 98.7%, B4C and (Ti 0.8 Mo 0.2 The total electromagnetic shielding effectiveness (SE T ) exceeds 43dB in the entire X-band, which means that it can shield more than 99.994% of X-band electromagnetic waves. Its main electromagnetic shielding mechanism is absorption loss. In the entire X-band, the absorption loss (~29dB) is significantly higher than the reflection loss (~14dB). At high temperature (700℃), the total electromagnetic shielding effectiveness (SE T ) exceeds 32dB in the entire X-band, which means that it can shield more than 99.93% of X-band electromagnetic waves. Its main electromagnetic shielding mechanism is absorption loss. In addition, the composite ceramic has a high specific hardness (10.06GPa·cm 3 ·g -1 ), specific strength (176MPa·cm 3 ·g -1 ) and specific fracture toughness (1.404MPa·m 1 / 2 cm 3 ·g -1These properties show that the B4C-(Ti 0.8 Mo 0.2 )B2 composite ceramic is a lightweight, multifunctional ceramic material that has both high-temperature electromagnetic shielding and load-bearing functions.
[0087] The above are only preferred embodiments of the present invention. It should be noted that the above preferred embodiments should not be regarded as limiting the present invention, and the protection scope of the present invention should be based on the scope defined by the claims. For ordinary technicians in this technical field, several improvements and modifications can be made without departing from the spirit and scope of the present invention, and these improvements and modifications should also be regarded as the protection scope of the present invention.
Claims
1. A lightweight boron carbide / titanium diboride-based composite ceramic with both high-temperature electromagnetic shielding and load-bearing functions, characterized in that: The composite ceramic is composed of B4C and single phase (Ti x M 1-x )B2 solid solution as the main component, wherein M is any one of Cr, Mo, Ni, Zr, Mn, W, Ta, Hf, V, Nb and Sc, and 0.5≤x≤1.
2. The lightweight boron carbide / titanium diboride-based composite ceramic with both high-temperature electromagnetic shielding and load-bearing functions according to claim 1 is characterized in that: The composite ceramic contains B4C and (Ti x M 1-x )The molar ratio of B2 is 1:0.5 to 1:1.
5.
3. The lightweight boron carbide / titanium diboride-based composite ceramic with both high-temperature electromagnetic shielding and load-bearing functions according to claim 1, characterized in that: The density of the composite ceramic is 2.9-4.9 g / cm 3 .
4. The lightweight boron carbide / titanium diboride-based composite ceramic with both high-temperature electromagnetic shielding and load-bearing functions according to claim 1, characterized in that: The specific hardness of the composite ceramic is 8.7 to 13.5 GPa·cm 3 ·g -1 , specific strength is 160~210MPa, specific fracture toughness is 1.2~2.0MPa·m 1 / 2 cm 3 ·g -1 .
5. The lightweight boron carbide / titanium diboride-based composite ceramic with both high-temperature electromagnetic shielding and load-bearing functions according to claim 1, characterized in that: At room temperature, the composite ceramic has a total electromagnetic shielding effectiveness of more than 40 dB in the X-band, and can shield more than 99.99% of X-band electromagnetic waves; at a high temperature of 700° C., the composite ceramic has a total electromagnetic shielding effectiveness of more than 30 dB in the X-band, and can shield more than 99.9% of X-band electromagnetic waves.
6. The lightweight boron carbide / titanium diboride-based composite ceramic with both high-temperature electromagnetic shielding and load-bearing functions according to claim 1, characterized in that: There are a large number of nano twins and stacking faults in the B4C of the composite ceramic. x M 1-x )There are lattice distortion and high-density dislocations in B2.
7. A method for preparing a lightweight boron carbide / titanium diboride-based composite ceramic having both high-temperature electromagnetic shielding and load-bearing functions as claimed in any one of claims 1 to 6, characterized in that: The preparation method includes any one of the following three methods: Method 1: Step 1.1, weighing and mixing one of commercially available Cr3C2, Mo2C, Ni3C, ZrC, Mn3C, WC, TaC, HfC, VC and NbC powders and TiC powder according to the chemical reaction equation (1), adding an organic solvent and a grinding ball, and mixing by ball milling for a certain period of time to obtain a powder slurry, and then drying and sieving by rotary evaporation to obtain a uniformly mixed powder; xTiC+(1-x)MC y =(Ti x M 1-x )C x+y-xy (1) Step 1.2: dry-press and vacuum-calcine the mixed powder obtained in step 1.1 to obtain (Ti x M 1-x )C x+y-xy The powder block is crushed, ground and sieved to obtain (Ti x M 1-x )C x+y-xy Powder; Step 1.3: The (Ti x M 1-x )C x+y-xy The powder and commercially available B powder and B4C powder are weighed and mixed according to the chemical reaction equation (2), and an organic solvent and grinding balls are added. After ball milling for a certain period of time, a powder slurry is obtained, and then the powder is dried by rotary evaporation and sieved to obtain a uniformly mixed powder. (Ti x M 1-x )C x+y-xy +(2+4x+4y-4xy)B+zB4C=(Ti x M 1-x )B2+(x+y-xy+z)B4C (2) In formula (1) and formula (2), 0.5≤x≤1, y=0.33, 0.5, 0.67 or 1, 0.67≤x+y-xy+z≤2; Step 1.4, pouring the mixed powder obtained in step 1.3 into a graphite mold or forming it by dry pressing or cold isostatic pressing, and then hot pressing sintering, spark plasma sintering or pressureless sintering at a certain temperature and pressure to obtain a lightweight boron carbide / titanium diboride-based composite ceramic with both high-temperature electromagnetic shielding and load-bearing functions; Method 2: Step 2.1, weigh and mix one of the commercially available CrB2, MoB2, ZrB2, MnB2, WB2, TaB2, HfB2, VB2, NbB2 and ScB2 powders with TiB2 powder and B4C powder according to the chemical reaction equation (3), add an organic solvent and a grinding ball, and mix the mixture by ball milling for a certain period of time to obtain a powder slurry, and then dry and sieve the mixture by rotary evaporation to obtain a uniformly mixed powder; <h2 style=";text-align:left;direction:ltr">xTiB2+(1-x)MB2+mB4C=(Ti<h2 style=";text-align:left;direction:ltr"> x <h2 style=";text-align:left;direction:ltr"> M<h2 style=";text-align:left;direction:ltr"> 1-x <h2 style=";text-align:left;direction:ltr"> (3) B2+mB4C In formula (3), 0.5≤x≤1, 0.67≤m≤2; Step 2.2, pouring the mixed powder obtained in step 2.1 into a graphite mold or forming it by dry pressing or cold isostatic pressing, and then hot pressing sintering, spark plasma sintering or pressureless sintering at a certain temperature and pressure to obtain a lightweight boron carbide / titanium diboride-based composite ceramic with both high-temperature electromagnetic shielding and load-bearing functions; Method 3: Step 3.1, weighing and mixing one of the commercially available Cr2O3, Mo2O3, NiO, ZrO2, MnO, WO3, Ta2O5, HfO2, V2O5, Nb2O5 and Sc2O3 powders with TiO2 powder, B4C powder, carbon powder or graphite powder according to the chemical reaction equation (4); then, putting the weighed powder, an appropriate amount of organic solvent and a certain amount of grinding balls into a ball mill, ball milling and mixing for a certain period of time to obtain a powder slurry, and rotary evaporating, drying and sieving to obtain a uniformly mixed powder; xTiO2+(1-x)MO p +(2x+p-px-0.5)C+(0.5+m)B4C=(Ti x M 1-x )B2+mB4C+(2x+p-px)CO (4) In formula (4), 0.5≤x≤1, 0.67≤m≤2, p=1, 1.5, 2, 2.5 or 3; Step 3.2: pour the mixed powder obtained in step 3.1 into a graphite mold, and perform hot pressing sintering or spark plasma sintering on it through multiple steps of heat preservation at a certain temperature and pressure to obtain a lightweight boron carbide / titanium diboride-based composite ceramic with both high-temperature electromagnetic shielding and load-bearing functions.
8. The method for preparing the lightweight boron carbide / titanium diboride-based composite ceramic with both high-temperature electromagnetic shielding and load-bearing functions according to claim 7, characterized in that: The purity of all commercially available raw materials in steps 1.1, 1.3, 2.1 and 3.1 is ≥99%, and the average particle size is 0.1-10 μm; the ball milling mixing time in steps 1.1, 1.3, 2.1 and 3.1 is 2-24 hours.
9. The method for preparing the lightweight boron carbide / titanium diboride-based composite ceramic with both high-temperature electromagnetic shielding and load-bearing functions according to claim 7, characterized in that: In the steps 1.4 and 2.2, the sintering temperature is 1700-2100°C, the sintering pressure is 0-200MPa, the holding time is 10-120min, the sintering environment is vacuum or argon atmosphere, and the heating rate is 10-200°C / min; in the step 1.2, the vacuum calcination temperature is 1200-1900°C, and the calcination time is 0.5-2h.
10. The method for preparing the lightweight boron carbide / titanium diboride-based composite ceramic with both high-temperature electromagnetic shielding and load-bearing functions according to claim 7, characterized in that: The sintering system in step 3.2 is as follows: first, the temperature is raised to 1500-1800°C at a heating rate of 10-200°C / min, and after being kept at this temperature for 10-90 minutes, the temperature is further raised to 1700-2100°C at a heating rate of 10-200°C / min, and the sintering pressure is uniformly increased to 30-200MPa, and then maintained at this temperature and pressure for 10-120 minutes, and finally cooled to room temperature with the furnace. The sintering environment conditions are vacuum or argon atmosphere.